The Future of Non-Union Repair: Synthetic Bone Grafts as Biomaterial-Based Solutions for Human Fracture Healing - I Putu Oka Pramudya; Komang Adi Praja Semara Putra (CV. Publikasi Indonesia, 2026)
Fracture non-union remains a complex orthopedic problem that often requires both mechanical stability and biological augmentation. Synthetic bone grafts have emerged as biomaterial-based alternatives or adjuncts to autologous grafting because they are widely available, avoid donor-site morbidity, and can be engineered for Oste conduction, controlled resorption, and local drug delivery. This systematic literature review and proportional meta-analysis evaluated the types and clinical impact of synthetic bone grafts used in human fracture non-union and post-traumatic bone defect repair. A systematic search of PubMed, Scopus, and Google Scholar was performed for English-language studies published from 2021 to 2026. Eligible studies included human clinical reports using hydroxyapatite, beta-tricalcium phosphate, biphasic calcium phosphate, calcium sulfate, bioactive glass, injectable bone cement, antibiotic-loaded grafts, or composite/3D-printed scaffolds. The primary outcome was union or consolidation proportion, with secondary outcomes including time to union, infection control, complications, reoperation, and functional recovery. From 6,665 records, 21 studies met the eligibility criteria. Synthetic grafts generally demonstrated favorable outcomes, with most studies reporting union rates above 75% and several achieving complete union. The pooled union efficacy from 15 quantitative observations was 90.4% (95% CI: 84.2–96.7%). However, heterogeneity was high (I² = 76.5%), reflecting variation in graft material, defect size, infection status, fixation strategy, and adjunct use. Synthetic bone grafts are promising osteoconductive scaffolds for fracture non-union repair, particularly as graft extenders, antimicrobial carriers, or patient-specific constructs. Nevertheless, their limited intrinsic osteogenic and Oste inductive capacity means they are best used with stable fixation and appropriate biological or antimicrobial augmentation.